An experimental, behavioral, and chemical analysis of food limitations in mutualistic Crematogaster ant symbionts inhabiting Macaranga host plants. Issue 2 (7th February 2023) - Houadria, Mickal Y. I.; Barone, Giulio; Fayle, Tom M.; Schmitt, Thomas; Konik, Petr; Feldhaar, Heike
Abstract: Obligate mutualistic plant–ants are often constrained by their plant partner's capacity to provide resources. However, despite this limitation, some ant partners actively reject potential prey items and instead drop them from the plant rather than consuming them, leaving the ants entirely reliant on host plant‐provided food, including that provided indirectly by the symbiotic scale insects that ants tend inside the plants. This dependency potentially increases the efficiency of these ants in defending their host. We hypothesize that if this ant behavior was beneficial to the symbiosis, prey rejection by ants would be observed across multiple plant host species. We also hypothesize that plant‐provided food items and symbiotic scale insects from other ant plants should be rejected. We address these hypotheses in the Crematogaster ant– Macaranga plant system, in which plants provide living space and food, while ants protect plants from herbivory. We observed food acceptance and rejection behavior across five ant species and three plant host species. Ants were offered three types of food: termites as a surrogate herbivore, symbiotic scale insects, and nutritious food bodies (FB) produced by different host plant species. The unique ant species living in M. winkleri was the most likely to reject food items not provided by the plant species, followed by ants in M. glandibracteolata, while ants in M. pearsonii accepted most items offered to them. Using stable isotopes, chemical cues, and proteomic analyses, we demonstrate that this behavior was not related to differences between plant species in nutritional quality or composition of FB. Isotopic signatures revealed that certain species are primary consumers but other ant species can be secondary consumers even where surrogate herbivores are rejected, although these values varied depending on the ant developmental stage and plant species. Macaranga pearsonii and M. glandibracteolata, the two most closely related plant species, had most similar surface chemical cues of FB. However, M. glandibracteolata had strongest differences in food body nutritional content, isotopic signatures, and protein composition from either of the other two plant species studied. Taken together we believe our results point toward potential host coercion of symbiont ants by plants in the genus Macaranga Thouars (Euphorbiaceae). Abstract : Understanding why within an ant–plant system, some symbiotic ants have different behaviors and diets. We demonstrate that this depends on the plant host rather than the ant species.